Activated sintering of magnesium oxide obtained from seawater - Martinac, Vanja (Materiali in tehnologije, 2007)
The process of isothermally sintering magnesium oxide obtained from seawater by substoichiometric (where precipitation of magnesium hydroxide took place with 80 % of the stoichiometric quantity of dolomite lime) and by overstoichiometric precipitation (which took place with 120 % of the stoichiometric quantity of dolomite lime) was examined, with the addition of mass fractions (1, 2 and 5) % TiOsub2, at temperatures in the range 1550-1750 °C, with (1, 3 and 5) h of soaking at the maximum temperature. The process was followed by a determination of the product density, as well as of the Bsub{2}Osub{3} content in the sintered samples. The results indicate that besides favorably affecting the density of the sintered samples, the addition of TiOsub2, with increasing temperature and soaking time, also significantly reduces the B2O3 content in the sintered magnesium oxide obtained from seawater. A statistical analysis of the obtained data was performed with the "Statistica" package in order to obtain a model of the density (r) of sintered samples of magnesium oxide relative to the temperature (t), time of isothermal heating (t), and thepercentage of added TiOsub2 (w).
Keywords: usedanje; magnezijev oksid; apno; titanov dioksid; sintranje